SISTEM INFORMASI PENGOLAHAN DATA BANK SAMPAH (Study Kasus : Bank Sampah Wirabuana, Kel. Lapadde, Kec.Ujung, Kota Parepare - Andi, Wafiah; Yusrin, Yusrin (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Garbage is leftover material that is produced from a production process both industrial and household. Then need treatment to overcome the problems that arise from waste, one of which is the existence of a garbage bank. In processing data in a garbage bank, it is still done manually by recording it with books. Therefore, along with the rapid advancement of technology, a web-based system is created that can help the process of waste transactions at the garbage bank. In the process of making the system, a research was carried out at the Wirabuana Garbage Bank, Ujung District, Lapadde Subdistrict, Parepare City. This research uses the method of observation, data collection and interviews The results of this study using black box testing showed that the functional system was running well and was able to follow the data processing system in accordance with the processing of wirabuana waste bank data and assisted officers in serving balance checking transactions and exchanging balances into basic needs effectively. which is web based with PHP programming language.